Robust Design of Spaghetti Products based on Consumer Needs - Nur Kartika Indah Mayasti; Mirwan Ushada; Makmudun Ainuri (Department Industrial Engineering, University of Muhammadiyah Malang, 2020)
To produce competitive advantage, a product has to be designed according to the criteria of consumer needs. The results of identifying consumer needs become technical requirements and target specifications in robust product design. The purpose of this research was to propose a robust design of gluten-free spaghetti product concept using the Taguchi method. The selection of factors and experimental levels utilized the zero one matrix and the evaluation matrix. The results showed that the priority quality attributes required by consumers include good product display, nutrition, acceptable taste, competitive prices, and made from local ingredients. Product specifications that are targeted at product quality are closer to commercial spaghetti products. Based on the experimental design, four factors and three levels with an orthogonal matrix (Taguchi) L9 (34) resulted in 9 product concepts. The selected concept has confirmed the quality of its spaghetti products.